Mathematics for informatics and computer science - Audibert, Pierre, 1941- (London : Wiley, 2013)
How many ways do exist to mix different ingredients, how many chances to win a gambling game, how many possible paths going from one place to another in a network? To this kind of questions Mathematics applied to computer gives a stimulating and exhaustive answer. This text, presented in three parts (Combinatorics, Probability, Graphs) addresses all those who wish to acquire basic or advanced knowledge in combinatorial theories. It is actually also used as a textbook.
3.9.1. Exercise 1: words with different successive letters3.9.2. Exercise 2: repeated purchases with a given sum of money; 3.10. Return to permutations; 3.11. Gray code; Chapter 4. Enumeration by Tree Structures; 4.1. Words of length n, based on N letters 1, 2, 3, ..., N, where each letter is followed by a higher or equal letter; 4.2. Permutations enumeration; 4.3. Derangements; 4.4. The queens problem; 4.5. Filling up containers; 4.6. Stack of coins; 4.7. Domino tiling a chessboard; Chapter 5. Languages, Generating Functions and Recurrences; 5.1. The language of words based on two letters
5.7.3. Language of words made from arrangements taken from n distinct and non-repeated letters a, b, c, etc., where these words are shorter than or equal to n.
Print version record.
John Wiley and Sons
Keywords: Computer science -- Mathematics; Informatique; Computer science -- Mathematics